The management of primary sclerosing cholangitis. - Chapman, R (2003)
Primary sclerosing cholangitis (PSC) is a chronic cholestatic hepatobiliary disease that usually progresses to biliary cirrhosis and liver failure; it also predisposes to cholangiocarcinoma. The cause of PSC is unknown, although evidence suggests that the tissue damage is mediated by the immune system. There is an unexplained close association between PSC and inflammatory bowel disease, particularly in ulcerative colitis, which coexists in the majority of patients with PSC. No medical therapy has been proven to halt or reverse disease progression; however, recent preliminary evidence suggests that ursodeoxycholic acid (UDCA) in a high dose of 20 to 25 mg/kg may slow the disease process. Evidence from a pilot study suggests that the combination of UDCA and immunosuppressive therapy, such as prednisolone or azathioprine, may also increase efficacy. For patients with end-stage PSC, liver transplantation remains the only effective therapy, although there is clear evidence that PSC may recur in the liver allograft.